USING INTERACTIVE LEARNING METHODS IS A REQUIREMENT OF TIME - Karimova , Adolat Ibragimovna; Yaqubov, Odil Mengliyevich (Innovative Development in Educational Activities, 2023)
The article says about the need to work with today’s youth studying in secondary schools and universities in our country, using not only traditional, but also modern, innovative technologies. One of these technologies is interactive teaching methods.